Shared Representations in Athletes: Segmenting Action Sequences From Taekwondo Reveals Implicit Agreement - Stadler, Waltraud; Kraft, Veit S.; Be’er, Roee; Hermsdörfer, Joachim; Ishihara, Masami (Frontiers in Psychology, 2021)
How do athletes represent actions from their sport? How are these representations structured and which knowledge is shared among experts in the same discipline? To address these questions, the event segmentation task was used. Experts in Taekwondo and novices indicated how they would subjectively split videos of Taekwondo form sequences into meaningful units. In previous research, this procedure was shown to unveil the structure of internal action representations and to be affected by sensorimotor knowledge. Earlier studies found experts to integrate over longer episodes which resulted in a lower number of single units, i.e., larger grain size of segmentation. Moreover, we expected higher agreement among experts on where to place segmentation marks, i.e., boundaries. In line with this hypothesis significantly more overlap of boundaries was found within the expert group as compared to the control group. This was observed even though the interindividual differences in the selected grain size were huge and expertise had no systematic influence here. The results suggest that shared semantic knowledge was underlying the strong agreement among experts. They might have benefitted from sensorimotor skills which allowed to simulate the observed actions more precisely. These interpretations are descriptively supported by the participants’ statements about features which guided segmentation and by an overlap of the group’s agreed boundaries with those of an experienced referee. The study shows that action segmentation can be used to provide insights into structure and content of action representations specific to experts. The mechanisms underlying shared knowledge among Taekwondoists and among experts in general are discussed on the background of current theoretic frameworks.